Are changes in glycaemic control associated with diabetes‐specific quality of life and health status in screen‐detected type 2 diabetes patients? Four‐year follow up of the ADDITION‐Cambridge cohort. Issue 1 (January 2015) - Kuznetsov, L.; Long, G. H.; Griffin, S. J.; Simmons, R. K.
Abstract Background Interventions that improve HbA1c levels do not necessarily improve health‐related quality of life (QoL). This issue may be particularly relevant in asymptomatic diabetes patients detected earlier in the course of the disease. Methods HbA1c, diabetes‐specific QoL (ADDQoL) and health status were measured in 510 screen‐detected diabetes patients from the ADDITION‐Cambridge trial at 1 and 5 years post diagnosis. Multivariable logistic/linear regression was used to quantify the longitudinal association between change in HbA1c from 1 to 5 years and ADDQoL and health status at 5 years, adjusting for age, sex, education and trial group; alcohol consumption, smoking, physical activity, plasma vitamin C, HbA1c, ADDQoL or health status at 1 year, and glucose‐lowering medication at 5 years. Results From 1 to 5 years, median HbA1c interquartile range increased from 6.3% (5.9–6.8) to 6.8% (6.4–7.4); the median ADDQoL score and mean health status physical health summary score decreased from ‐0.4 (‐1 to ‐0.08) to ‐0.5 (‐1.08 to ‐0.09) (suggesting an adverse impact of diabetes on QoL) and by ‐0.79 (8.94) points, respectively. Increases in HbA1c were independently associated with reporting a negative impact of diabetes on QoL (OR = 1.38, 95% CI: 1.03 to 1.85) but not with the health status summary scores. Conclusions Increases in HbA1c from 1 to 5 years post‐diagnosis were independently associated with increased odds of reporting a negative impact of diabetes on QoL. While our results suggest that efforts to reduce HbA1c do not adversely affect health‐related QoL, large numbers of participants still report a negative impact of diabetes on their QoL 5 years post‐diagnosis. © 2014 The Authors. Diabetes/Metabolism Research and Reviews published by John Wiley & Sons, Ltd.